Kepemimpinan Menumbuhkan Kreatifitas Siswa dengan Pemanfaatan Media Sosial: Leadership Grows Student Creativity by Utilizing Social Media - Nilasari, B. Medina; Darasih, Ratna; Henny, Deliza; Walidaeni, Ihsanul; Pongoh, Andri Sebastian; Rahmawati, Ulfi Naria; Sasantyarini, Sasantyarini (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Teachers, school principals, and heads of foundations will help create change toward achieving school reform. Change can start by fostering creativity, in this case, through social media. The use of social media needs to be understood from an early age. Knowledge and ability to use social media can be trained starting from junior high school level. Especially for schools that aim to produce entrepreneurs. Students can hone and channel their creative ideas through social media, such as making videos, photos, writing, etc. On YouTube, students can channel their creative ideas to make videos. Students can channel their creative ideas on Instagram by writing photos and even videos. Students can also use other applications on social media. This Community Service (PkM) activity aims to provide educational assistance students need at the Islamic Entrepreneurship Boarding School, Global Cahaya Nubuwah Insani Foundation - Purwakarta. Education is provided in the form of business leadership counseling and the use of social media, which would not be realized without the support of teachers, school principals, and foundations.